Implementation of an Eduliterasi Application for Children (Nusantara Science and Technology Proceedings, 2021)
During the current Covid-19 pandemic, digital technology plays an active role in online learning. In online learning, we can take advantage of technology even though it is limited by distance. Currently, we need a digital literacy system that helps children's learning, especially elementary school children. A child can learn online anywhere using a computer. Digital literacy can help children's development in terms of reading. Reading is a complex activity in students that can produce a new mindset after reading. However, there are not a few students who rarely read and there are also those whose reading interest has decreased due to the change in the learning system to distance learning. Educators can take advantage of digital literacy in increasing students' reading interest so that students can maximize online learning for learning development. This study focuses on how to design a web-based literacy information system to support children's learning to increase children's interest in reading and knowledge, which is called the “Eduliterasi” system. Utilizing this application can provide a direct reading experience and with many topics that can be read.